Efektivitas Program Bantuan Pangan Non Tunai Di Kelurahan Pantoloan Boya Kecamatan Tawaeli Kota Palu - Nurjannah; Nasrullah; Rachmad (JPS: Journal of Publicness Studies, 2026)
This study aims to determine the effectiveness of the Non-Cash Food Assistance (BPNT) Program in Pantoloan Boya Village, Tawaeli District, Palu City. The research method used was descriptive qualitative, with seven informants: the Village Head, Village Secretary, BPNT management staff, operator staff, Beneficiary Families (KPM), and members of the public who did not receive Non-Cash Food Assistance (BPNT). Data collection techniques included observation, interviews, and documentation. Primary and secondary data sources were used. Data analysis included data collection, data condensation, data presentation, and conclusion drawing. The theory used in this study is Ni Wayan Budiani (2007:53), which uses four indicators: Program Targeting Accuracy, Program Socialization, Program Objectives, and Program Monitoring. The results of the study indicate that the Program Targeting Accuracy has not been implemented effectively. Some recipients of assistance are still not properly targeted because some do not meet the recipient criteria but are still registered as recipients. The socialization program has been running effectively. Most of the Beneficiary Families (KPM) of the Non-Cash Food Assistance Program (BPNT) in Pantoloan Boya Village have participated in the socialization activities of the Non-Cash Food Assistance Program (BPNT) held by the Non-Cash Food Assistance Program (BPNT) officers. So that the Beneficiary Families (KPM) understand about the Non-Cash Food Assistance Program (BPNT). The indicators for achieving the program's objectives have been running effectively, sufficiently helping the community's economy, especially for underprivileged families. This assistance contributes to providing basic food needs so that it can reduce the burden of household expenses for beneficiary families. Program monitoring is carried out routinely on program implementation. The monitoring program is carried out starting from the aid distribution process, the availability of food supplies for Beneficiary Families (KPM) in Pantoloan Boya Village, Tawaeli District.